Effects of FER1L4-miR-106a-5p/miR-372-5p-E2F1 regulatory axis on drug resistance in liver cancer chemotherapy - Xu Wang; Yunfei Chen; Ke Dong; Yujing Ma; Qizhi Jin; Shujun Yin; Xiaoshi Zhu; Shan Wang (Elsevier, 2021)
Liver cancer presents a challenge in today's healthcare system. This study aimed at investigating the effects of Fer-1 like family member 4 (FER1L4) on chemotherapy resistance and liver cancer development by using clinically collected liver cancer tissues and commercially purchased human liver cancer cisplatin-resistant cell line HUH-7/DDP. Bioinformatics analysis, dual luciferase reporter gene assay, and RNA pull-down were applied to predict and verify the possible binding relationships. The expressions of FER1L4, E2F transcription factor 1 (E2F1), microRNA-106a-5p (miR-106a-5p), or miR-372-5p were altered in the cells, followed by flow cytometry, Cell Counting Kit-8 (CCK-8), and Transwell assays to evaluate apoptotic, proliferative, and invasive abilities in vitro and nude mice xenografts to observe tumor growth in vivo. FER1L4 was highly expressed and miR-106-5p and miR-372-5p were poorly expressed in tumor cells and tissues. FER1L4 knockdown or the overexpression of miR-106-5p and miR-372-5p inhibited the cancerous cell proliferation and invasion while promoting apoptosis. FERIL4 silencing increased the miR-106-5p/miR-372-5p expression to inhibit the E2F1-activated nuclear factor κB (NF-κB) pathway. Besides, overexpressing FER1L4 led to an increased tumor growth in nude mice, which was reversed by the NF-κB inhibitor pyrollidine dithiocarbamate (PDTC). In conclusion, the results indicated that FER1L4 could inhibit the expression of miR-106a-5p/miR-372-5p, to activate E2F1-mediated NF-κB pathway, leading to drug resistance in liver cancer.